An Investigation into the Prevalence of Migraine and Its Prophylactic Treatment Patterns in the Czech Republic: An Observational Study - Dolezil, David; Markova, Jolana; Klimes, Jiri; Pocikova, Zuzana; Dostal, Filip; Stepanova, Radka; Svobodnik, Adam (Journal of pain research, 2020)
PURPOSE: A national primary and secondary healthcare-level study in the Czech Republic has not yet been conducted to evaluate the prevalence of migraine. We analyzed the current treatment patterns (acute and prophylactic) in migraine patients and the number of migraine patients potentially eligible for treatment with recent calcitonin gene-related peptide (CGRP) pathway-targeted therapies. METHODS: This retrospective study utilized the Ministry of the Interior Health Insurance Fund claims database of the Czech Republic wherein every citizen is insured. Migraine patients with or without aura, and potentially on triptan therapy were included in this study (index years 2012-2016). The prevalence approach included all patients (new and old) present in each index year. Prophylactic therapies were followed f0or three and seven years prior to the index year, including the index year, until 2010. The incidence approach included all patients first diagnosed in each index year. Prophylactic therapies were followed for the next three years, including the index year, until 2017 following incidence approach. The primary endpoint of this study was to determine the rate of migraine prevalence and diagnosis for each index year during the period 2012-2016. The study also evaluated prophylactic and acute treatment patterns and comorbidities among patients in 2016. RESULTS: The rate of migraine prevalence was 1% and the rate of diagnosis was 0.2-0.4%. By prevalence approach, approximately 39% of the patients were on prophylactics, and 11.2% and 21.6% of the patient population had two prior treatment failures (three- and seven-year recall period, respectively). Antiepileptics (26%) and beta blockers (15.8%) were the most prescribed prophylactics, and sumatriptan was the predominant triptan used (12%) for acute treatment. CONCLUSION: Taking into account the number of inhabitants in the Czech Republic (10.7 million), there could be up to 23,000 adult patients eligible for novel CGRP therapies.
Keywords: prophylactics; triptans; CGRP; claims database